The near-complete genome assembly of Ampelopsis grossedentata provides insights into its origin, evolution, and the regulation of flavonoid biosynthesis - Yao, Zhi; Feng, Zhi; Wu, Fuwen; Zhang, Peiling; Wang, Qiye; Ai, Binling; Wang, Yiqiang; Li, Meng (Frontiers in Plant Science, 2025)
Ampelopsis grossedentata, native to southern China, is renowned for its therapeutic and nutritional benefits, often called the “king of flavonoids” due to its high dihydromyricetin content. The dried stems, leaves, and shoot tips, known as “vine tea,” are consumed as a health beverage and traditional remedy for colds and fever. In this study, we assembled a near-complete reference genome of A. grossedentata spanning 555.42 Mb, where Hi-C-based correction resolved 18 out of its 20 chromosomes into gap-free assemblies. The genome, anchored to 20 chromosomes, comprises 44 contigs with an N50 of 21.93 Mb and 28 scaffolds with an N50 of 30.45 Mb, containing 25,999 protein-coding genes and 62.62% repetitive sequences. The A. grossedentata experienced two whole-genome duplication (WGD) events: a whole-genome triplication event shared by the core angiosperms and a WGD event shared with Vitaceae family. Through transcriptome-metabolome integrated analysis, AgF3H1 gene was identified as playing a crucial role in the biosynthesis of dihydromyricetin (a flavanonol) in A. grossedentata. The AgF3H gene is essential for converting pentahydroxy flavones to dihydromyricetin within the flavonoid biosynthesis pathway in A. grossedentata, as confirmed by molecular docking results. Thus, we postulate that AgF3H1 serves as a pivotal regulatory gene in the dihydromyricetin biosynthetic pathway of A. grossedentata. These insights offer valuable genetic resources for the molecular breeding of A. grossedentata and enhance our comprehension of Vitaceae genomic evolution and flavonoid biosynthesis regulation in medicinal and nutritional plants.